2015
DOI: 10.1007/s10566-015-9311-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mental Health Among Low-Income, Minority Women Following Exposure to Multiple Natural Disasters in Early and Late Adolescence Compared to Adulthood

Abstract: Background High impact experiences following a natural disaster have been shown to influence later psychopathology. Individual-level factors such as age may also contribute to a disaster’s impact on mental health, though it is unclear whether young age confers a protective effect or represents a period of increased risk as compared to adulthood. Objective The present study evaluated the influence of adolescent age and hurricane experiences on mental health in the years following multiple hurricanes in the Ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
(79 reference statements)
3
28
0
1
Order By: Relevance
“…The results for mental health are consistent with a growing body of research demonstrating the phenomenon of cumulative disaster exposure (e.g., Harville et al., ; Jacobs & Harville, ). Further research is needed to understand the mechanisms by which cumulative disaster exposure leads to mental health symptoms.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The results for mental health are consistent with a growing body of research demonstrating the phenomenon of cumulative disaster exposure (e.g., Harville et al., ; Jacobs & Harville, ). Further research is needed to understand the mechanisms by which cumulative disaster exposure leads to mental health symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…The model that has received the most empirical support to date is a “cumulative” model wherein disasters influence health in a dose–response fashion. A series of studies by Harville and colleagues has illustrated the phenomenon of cumulative exposure for postdisaster mental health in the Gulf Coast (Harville et al., , ; Jacobs & Harville, ). First, among a sample of 102 women from Southern Louisiana, individuals who had experienced severe exposure (defined as being forced to evacuate or experiencing the death of a relative) to both Katrina and Hurricane Gustav, which struck the area in September 2008, had elevated levels of both PTSD and depression symptoms relative to those who experienced severe exposure to only one or neither disaster (Harville et al., ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, this line of post-disaster research demonstrates the need for a more robust local public health presence, particularly related to behavioral health outreach. Specifically, research demonstrates the need for improved public health surveillance, targeted outreach following an event, and long-term follow-up to prevent the cumulative exposures presented by multiple disasters [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Among the interesting findings is that based on locally–derived risk assessment data, the seafood from the Gulf of Mexico is safe to eat while one species of imported seafood is contaminated at levels of potential public health concern [28]. Furthermore, as an example of a non-chemical stressor, the largest cohort of GROWH pregnant and reproductive age women reported financial loss as the most significant negative effect of the DWH oil spill [29]. Consortia studies completed soon after the spill found individuals with spill-related income loss were more likely to experience poor psychosocial symptoms [30].…”
Section: Human Health Effectsmentioning
confidence: 99%